Propuesta de plan de mejoramiento basada en la metodología Seis Sigma para la disminución de defectos en el proceso de producción de la empresa amoblarte (2023)
The present work consisted of developing an improvement plan proposal based on the DMAIC process of the Lean Six Sigma methodology for the Amoblarte company in the city of Tunja, dedicated to the manufacture and marketing of office and school furniture, in which First of all, he carried out a general diagnosis of the company and its production process, as well as the identification of each of the variables present in each of its activities.